Building distribution strategies using distribution supply chain modelling - Ho, Tong Fatt. (2011)
Distribution supply chain model is an analytical model developed to investigate the impact that different physical network configurations have on the total distribution cost of Company XYZ as well as on its delivery turn-around-time. The model attempts to represent the distribution supply chains in the Asia Pacific by a basic network structure that comprises the supplier, regional hub, remote depot and customer region. By feeding in the necessary input data, such as line-item-fill rate, demand forecast, freight rate, transit time and lead time variability etc, together with a set of scenarios, the model arrives at different cost and turn-around-time results for different scenarios. The results are first validated against actual total cost and turn-around time before being used to extrapolate in time and space - projecting a few years ahead and adding depots, to see what the results are in cost and turn-around time.